2002
DOI: 10.1159/000047758
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale, a Possible Cause of Symptomatic Migraine: A Study of 74 Patients with Acute Ischemic Stroke

Abstract: Recent studies reported an increased prevalence of patent foramen ovale (PFO) in patients with migraine with aura (MA+). To investigate the possible relationship between MA+ and paradoxical embolism, we studied the prevalence of both conditions. Investigation of PFO was undertaken in 74 consecutive patients presenting with an acute stroke of undetermined origin. The patients were questioned about MA+ or migraine without aura (MA–) according to the criteria of the International Headache Society. Follow-up was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(69 citation statements)
references
References 18 publications
2
67
0
Order By: Relevance
“…Our results showing higher frequency of RLS/PFO in children with MA(+) are similar to other reports [1,9,29]. It is likely that the association of migraine and PFO is coincidental, because both disorders are frequent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showing higher frequency of RLS/PFO in children with MA(+) are similar to other reports [1,9,29]. It is likely that the association of migraine and PFO is coincidental, because both disorders are frequent.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, It is possible that unknown genetic factors predispose both to migraine and PFO leading to endocardial and endothelial malformation. Some studies confirmed the association between MA(+) and PFO by suppression of migraine symptoms in some patients after the closure of PFO [10,27,29,32]. However, the association between closure of PFO and decreased attacks of migraine is still a matter of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in both the prevalence and severity of migraine was reported following transcatheter vaso-occlusion of PAVMs [98]. A similar relationship between right-to-left shunt and migraine has been reported in patients with a patent foramen ovale [99, 100]. Presumably, PAVMs may increase the risk of migraine through the lack of trapping of vasoactive substances by bypassing the pulmonary capillary circulation, or alternatively through a genetic trait associated with both migraine and HHT.…”
Section: Clinical Manifestations and Complications Of Pavmsmentioning
confidence: 79%
“…Others, in a cohort of 74 cryptogenic stroke patients, found PFO in 59% of cases. A history of migraine with aura was more frequent in patients with PFO than in those without (36 vs. 13%, p = 0.03) [82]. Another case-control study included 113 patients with migraine with aura, 53 with migraine without aura, and 25 matched nonmigraine controls.…”
Section: Pfo and Migrainementioning
confidence: 99%